HEALING IN SOME PENTECOSTAL CHURCHES IN SOUTH-WESTERN NIGERIA - Owoeye, Saibu Ainde (European Scientific Journal, ESJ, 2012)
Healing and casting of demons are common among the Pentecostal believers in Nigeria especially among the leaders of Pentecostal Churches. The Deeper Christian Life Ministry, the Redeemed Christian Church of God and the Life Gate Ministries are known for their penchant for healing over the years. This paper looks at their healing activities in major areas especially in the area of terminal diseases like diabetes, hypertension, stroke, cardiovascular disorder and other malignant diseases like cancer, Acquired Immune Deficiency Syndrome (HIV/AIDS). The paper compares their healing activities for three consecutive years, to see the efficacy of their healing apparatus – prayer, faith. The research also highlights the areas where one church is better than others. The paper after assessment concludes by looking at the inadequacy of prayer in healing HIV/AIDS victims.